Inflammation and Microvasculopathy in Renal Ischemia Reperfusion Injury - Daniel Patschan; S. Patschan; G. A. Müller (Journal of Transplantation, 2012)
Acute renal failure (ARF) severely worsens prognosis of hospitalized patients. The most frequent cause of intrarenal ARF is transient or prolonged renal hypoperfusion (ischemia). Ischemia primarily affects the function and structure of tubular epithelial cells, which, in severe cases, is characterized by epithelial cell necrosis. Nevertheless, ischemia does not exclusively lead to alterations of epithelial cells but also causes interstitial inflammation and interstitial microvasculopathy. Both inflammation and microvasculopathy are particularly important in terms of postischemic kidney repair. Postischemic microvasculopathy is characterized by endothelial cell swelling with subsequent microvascular occlusion. Thus, reperfusion is inhibited (no-reflow phenomenon). Such endothelial cell dysfunction offers new therapeutic perspectives in ischemic ARF. Newer observations point towards the role of the so-called endothelial progenitor cells (EPCs) in the treatment of ARF. Systemic administration of EPCs to mice with bilateral renal ischemia mitigates postischemic endothelial cell dysfunction and protects animals from acute renal failure.